Διαφορά μεταξύ των αναθεωρήσεων του «Φαινόμενο Ντόπλερ»

 
::<math>\nu\,' = \left( \frac{v \pm v_O \cos\phi}{v \mp v_s \cos\theta} \right) \nu. \,</math>
 
{{hidden begin|title=Απόδειξη|toggle=left}}
Given <math>f = \left( \frac{c + v_\text{r}}{c + v_\text{s}} \right) f_0 \,</math>
 
Διαιρούμε με <math>c</math>
 
<math>f = \left( \frac{1 + \frac{v_\text{r}} {c}} {1 + \frac{v_\text{s}} {c}} \right) f_0 = \left( 1 + \frac{v_\text{r}}{c} \right) \left( \frac{1}{1 + \frac{v_\text{s}} {c}} \right) f_0 \,</math>
 
Εφόσον <math>\frac{v_\text{s}}{c} \ll 1</math> μπορούμε να αντικαταστήσουμε τη γεωμετρική επέκταση:
 
<math> \frac{1} {1 + \frac{v_\text{s}}{c}} \approx 1 - \frac{v_\text{s}}{c}</math>
{{hidden end}}
 
== Παράδειγμα ==
Ανώνυμος χρήστης